Budaya Organisasi dan Penerapan Akuntansi di Pemerintah Daerah di Aceh - Cut Alya Shafira; Syukriy Abdullah (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2022)
AbstractThis paper describes the relationship between organizational culture and the application of accounting in local government in Aceh. Aceh has a uniqueness and specificity that has implications for the implementation of government functions, such as: the existence of Islamic law, the acceptance of special autonomy funds and a long history as a great nation. Local governments in Aceh currently carry out public service and governance functions based on Law No. 11 of 2006 concerning the Government of Aceh, which does not apply in other areas. For this reason, several Regional Apparatus Work Units (SKPD) in Aceh do not exist in other provinces in Indonesia.Keywords: budaya organisasi, penerapan akuntansi, UU No. 11 Tahun 2006, satuan kerja perangkat daerah, syari’at Islam.